"Cargo-mooring" as an operating principle for molecular motors. (7th June 2015) - Lisowski, Bartosz; Kuśmierz, Łukasz; Żabicki, Michał; Bier, Martin
Abstract: Navigating through an ever-changing and unsteady environment, and utilizing chemical energy, molecular motors transport the cell׳s crucial components, such as organelles and vesicles filled with neurotransmitter. They generate force and pull cargo, as they literally walk along the polymeric tracks, e.g. microtubules. What we suggest in this paper is that the motor protein is not really pulling its load. The load is subject to diffusion and the motor may be doing little else than rectifying the fluctuations, i.e. ratcheting the load׳s diffusion. Below we present a detailed model to show how such ratcheting can quantitatively account for observed data. The consequence of such a mechanism is the dependence of the transport׳s speed and efficacy not only on the motor, but also on the cargo (especially its size) and on the environment (i.e. its viscosity and structure). Current experimental works rarely provide this type of information for in vivo studies. We suggest that even small differences between assays can impact the outcome. Our results agree with those obtained in wet laboratories and provide novel insight in a molecular motor׳s functioning. Abstract : Highlights: Experiments suggest that cargo dynamics play a role for kinesin׳s motion. We work out how chemical energy can be used to rectify the cargo׳s diffusion. Kinesin and its cargo interact cooperatively to move along the polymeric track. We derive the velocity as a function of load force, cargo size and buffer viscosity. Experimental observations appear consistent with our results.